Academic performance of online physical education learning during COVID-19 outbreak: systematic literature review - Jeki Haryanto; Edi Setiawan; Ruslan Abdul Gani; Padli Padli; Ifdil Ifdil (International Journal of Evaluation and Research in Education (IJERE), 2024)
In the COVID-19 outbreak, a strong learning strategy is essential to achieving success in student academic performance. This study aims to find out the academic performance of online physical education courses as the COVID-19 outbreak spreads globally. This study’s objective is to assess how online physical education performed during the COVID-19 pandemic. This study follows the preferred reporting items for systematic review and meta-analyses (PRISMA). Science Direct, Taylor and Francis online, PubMed, Scopus, Springer, and Wiley online library are the databases that are deployed to look for papers about studies. Online search references are found by using a procedure that involves typing in terms of physical education programs during the COVID-19 outbreak for each database. To achieve three articles as results after the screening procedure, the author’s selection criteria for inclusion and exclusion were applied to the search results from the 263 articles that were created from the complete database. The review’s conclusion is teaching online physical education during the COVID-19 outbreak still produces good academic performance. The usage of technology to teach all of the students during COVID-19 online is the primary reason for maintaining student academic performance.